Pemanfaatan Teknologi Android Dalam Meningkatkan Kualitas Wisata Sejarah Jejak Bung Karno Di Kabupaten Ende Melalui Metode User Centered Design - Natalia Kristiani Tandafatu; Hilarius Alfan; Yosephina Kejang (Universitas Nusa Nipa Maumere, 2025)
The purpose of this study is to analyze the potential and development strategies of the historical tourism site “Jejak Bung Karno” (The Footsteps of Bung Karno) in Ende Regency, as well as to design an Android-based digital media to enhance the overall visitor experience. Ende is recognized for its profound historical value as the place where the foundational ideas of Pancasila were first conceived, and it is home to several important sites such as the Bung Karno Exile House and the Pancasila Reflection Park. However, the management of this destination remains suboptimal, particularly in terms of promotion, the application of digital technology, and the delivery of engaging tourist information. The user interface design was developed using Figma software, while user experience testing was conducted through the User Experience Questionnaire (UEQ) involving 35 participants. The results indicate that the Attractiveness (2.027) and Perspicuity (3.804) aspects received “excellent” ratings, while Efficiency, Dependability, Stimulation, and Novelty were categorized as “above average.” These findings suggest that the application interface design aligns well with user needs and preferences. Furthermore, the study highlights that the implementation of Android-based technology contributes positively to the digitalization of historical tourism, broadens promotional reach, and strengthens the identity of “Ende Bumi Pancasila” as an educational and cultural tourism destination in the era of digital transformation.